THE IMPORTANCE OF ENGLISH IN GLOBAL MARKET - Azimdjanova Farangiz,; Nurova Maftuna, (TADQIQOTLAR, 2025)
Introduction In  today’s  interconnected  world,  language  plays  a  key  role  in  international cooperation,  trade,  and  communication.  Among  all  global  languages,  English  has emerged as the dominant medium in global markets. From multinational corporations to small exporters, English is essential for negotiating, marketing, and establishing global partnerships. This article explores why English holds such an influential position in international trade and how it contributes to business success worldwide.